(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2026)
Banana plants are among the tropical fruit crops widely cultivated in Indonesia. Banana cultivation is not immune to pests that can reduce banana production. One pest that attacks banana plants is the banana skipper (Erionota thrax L.). This pest is characterized by its method of attacking plants: rolling up banana leaves. Indonesia is known as one of the world’s banana producers. The purpose of this study was to determine the level of attack caused by leaf-rolling caterpillars on plantain trees in South Sumatra. This study used the Purposive Sampling method, while the data collection technique was carried out by taking samples from banana plants (Musa acuminata) affected in South Sumatra, consisting of 5 regencies/cities, namely Banyuasin Regency, Muara Enim Regency, Ogan Ilir Regency, East Ogan Komering Ulu Regency, and Lubuk Linggau City. Based on the research results, the highest percentage of affected banana clumps was in East OKU Regency at 29%, while the lowest was in Lubuk Linggau City at 13%. The highest number of affected banana stems was in Ogan Ilir Regency at 26%, and the lowest was in Banyuasin Regency at 11%. The highest percentage of attacks was in Lubuk Linggau City at 46.67%, and the lowest was in Banyuasin Regency at 34.78%. Lubuk Linggau is located in the lowlands and midlands, which provide E. thrax with suitable temperatures, resulting in healthier banana plants and better food for the larvae.